2012
DOI: 10.3390/insects3020473
|View full text |Cite
|
Sign up to set email alerts
|

Shared Ancestry of Symbionts? Sagrinae and Donaciinae (Coleoptera, Chrysomelidae) Harbor Similar Bacteria

Abstract: When symbioses between insects and bacteria are discussed, the origin of a given association is regularly of interest. We examined the evolution of the symbiosis between reed beetles (Coleoptera, Chrysomelidae, Donaciinae) and intracellular symbionts belonging to the Enterobacteriaceae. We analyzed the partial sequence of the 16S rRNA to assess the phylogenetic relationships with bacteria we found in other beetle groups (Cerambycidae, Anobiidae, other Chrysomelidae). We discuss the ecology of each association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…We found that the symbiont gene exhibits remarkably AT-biased nucleotide composition and significantly accelerated molecular evolution, which are suggestive of degenerative evolution of the symbiont genome. A morphologically similar bacterial symbiont was also reported from a chrysomelid leaf beetle [ 69 ], but that symbiont was recently shown to be a member of the γ-Proteobacteria [ 70 , 71 ], suggesting that these rosette-shaped bacterial symbionts have independent evolutionary origins. The rosette-shaped symbiont of the leaf beetle also exhibited a remarkably AT-biased nucleotide composition and a significantly accelerated rate of molecular evolution [ 71 ].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We found that the symbiont gene exhibits remarkably AT-biased nucleotide composition and significantly accelerated molecular evolution, which are suggestive of degenerative evolution of the symbiont genome. A morphologically similar bacterial symbiont was also reported from a chrysomelid leaf beetle [ 69 ], but that symbiont was recently shown to be a member of the γ-Proteobacteria [ 70 , 71 ], suggesting that these rosette-shaped bacterial symbionts have independent evolutionary origins. The rosette-shaped symbiont of the leaf beetle also exhibited a remarkably AT-biased nucleotide composition and a significantly accelerated rate of molecular evolution [ 71 ].…”
Section: Discussionmentioning
confidence: 66%
“…The similarity of the peculiar symbiont morphology, despite the phylogenetically distant insect hosts, raises the question of whether the rosette-shaped symbiotic bacteria of bostrichid beetles are phylogenetically related to those of the chrysomelid beetle [ 1 ]. Recently, molecular phylogenetic analyses showed that the symbiont of B. obscurus is a member of the class γ-Proteobacteria [ 70 , 71 ]. We show in the present study that the symbiont of R. dominica belongs to the Bacteroidetes, which is phylogenetically distant from the γ-Proteobacteria (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in leaf beetles have shown a phylogenetic linkage between the host and foregut‐inhabiting, extracellular symbionts (Fukumori, Koga, Nikoh, & Fukatsu, ; Kölsch & Pedersen, ). Specifically, evidence for cospeciation has been found in the chrysomelid subfamilies Cassidinae, Eumolpinae, Sagrinae, and Donaciinae (Fukumori et al, ; Kölsch & Synefiaridou, ; Salem et al, ). Whether a symbiosis similar to Stammera is present in all subfamilies or beetle lineages remains unclear.…”
Section: Herbivore Co‐option Of Gut‐associated Bacteria To Facilitatementioning
confidence: 99%
“…As for weevils, an ancient gammaproteobacterial endosymbiont clade, Nardonella spp., found in diverse weevils ( 24 , 25 ), a gammaproteobacterial endosymbiont, Sodalis pierantonius , that presumably replaced the original Nardonella endosymbiont in the lineage of grain weevils of the genus Sitophilus ( 26 , 27 ), and another gammaproteobacterial endosymbiont, Curculioniphilus buchneri , that also replaced the original Nardonella endosymbiont in the lineage of acorn weevils of the genus Curculio and allied species ( 28 30 ), have been described. As for leaf beetles, a gammaproteobacterial endosymbiont clade, Macropleicola spp., associated with reed beetles of the subfamily Donaciinae ( 31 33 ), and several other gammaproteobacterial endosymbionts ( 34 , 35 ) have been reported.…”
Section: Introductionmentioning
confidence: 99%